1988
DOI: 10.1126/science.3285469
|View full text |Cite
|
Sign up to set email alerts
|

Aldolase Activity of a Plasmodium falciparum Protein with Protective Properties

Abstract: Immunization with a 41-kilodalton blood stage antigen (p41) of Plasmodium falciparum induces immunity to malaria in monkeys. However, antigenic polymorphism and repetitive amino acids commonly found in protective antigens complicate vaccine development. The gene encoding p41 has now been cloned and analyzed. Sequencing and hybridization studies revealed that the gene structure is highly conserved in 14 parasite isolates from three continents. This finding and the lack of repetitive amino acids in the translate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
24
0

Year Published

1989
1989
2011
2011

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 81 publications
(24 citation statements)
references
References 20 publications
0
24
0
Order By: Relevance
“…Accumulating evidence suggests that intracellular antigens can serve as protecting epitopes against parasitic diseases (Dessein et al 1988;Wain et al 1994;Sher et al 1989;Certa et al 1988). Lubega et al (2002) demonstrated that mice vaccinated with native tubulin from T. brucei could be protected against T. brucei, T. congolense, and T. rhodesiense challenges.…”
Section: Discussionmentioning
confidence: 99%
“…Accumulating evidence suggests that intracellular antigens can serve as protecting epitopes against parasitic diseases (Dessein et al 1988;Wain et al 1994;Sher et al 1989;Certa et al 1988). Lubega et al (2002) demonstrated that mice vaccinated with native tubulin from T. brucei could be protected against T. brucei, T. congolense, and T. rhodesiense challenges.…”
Section: Discussionmentioning
confidence: 99%
“…Cloning and a high level of expression of genes encoding P. falciparum enzyme activities would permit studies on the structure and function of the parasiteÕs metabolic enzymes, eventually leading to identification of drugs that can selectively inhibit certain parasitic enzymes. The focus has been on cloning glycolytic pathway genes in P. falciparum because it is known that it relies on anaerobic glycolysis for energy production during the erythrocytic stages (Certa et al 1988; Kaslow and Hill 1990;Hicks et al 1991). However, its genome sequence revealed that many other biochemical pathways could also be reconstructed , suggesting the existence of yet uncharacterized pathways that may be essential for the parasiteÕs pathogenicity.…”
Section: Introductionmentioning
confidence: 98%
“…The other recombinant protein included in this study is a protein ofMr 41,000 (termed p41), which was identified as the aldolase of the parasite (4,11). The parasite-derived antigen preparation gave a marked degree of protection against malaria in immunized Saimiri monkeys (4).…”
mentioning
confidence: 99%
“…The parasite-derived antigen preparation gave a marked degree of protection against malaria in immunized Saimiri monkeys (4). Probably for functional reasons, the entire polypeptide sequence is highly conserved in all P. falciparum isolates analyzed (11). The central function of aldolase for parasite metabolism makes it unlikely that mutants due to immunoselection will appear after immunization.…”
mentioning
confidence: 99%
See 1 more Smart Citation